2009
DOI: 10.1108/09654280911001167
|View full text |Cite
|
Sign up to set email alerts
|

The usability of medicine education assignments for seven to nine year‐old children

Abstract: PurposeA medicine education web site was developed during a research project in 2002–2004 to help teachers in primary and junior secondary schools to teach children the proper use of medicines. However, there was a need to develop further the assignments for the youngest schoolchildren. The aim of this study is to evaluate the usefulness of three medicine education assignments created for seven to nine year‐old children, and to describe how children experienced them.Design/methodology/approachTriangulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(22 reference statements)
0
9
0
1
Order By: Relevance
“…The prevalence of medicine use in children, both prescribed and over-the-counter (OTC) is reported to be high (Ha¨meen-Anttila et al, 2009). For example, one study in the USA found that 54% of children younger than three years old were given an OTC medicine during a period of 30 days (Kogan et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of medicine use in children, both prescribed and over-the-counter (OTC) is reported to be high (Ha¨meen-Anttila et al, 2009). For example, one study in the USA found that 54% of children younger than three years old were given an OTC medicine during a period of 30 days (Kogan et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it became an obligatory subject in junior secondary schools and in primary schools, through a new curriculum. This new topic creates challenges for teachers, who usually have not had any formal education about medicines during their studies (Ha¨meen-Anttila et al, 2009;Ha¨meen-Anttila et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Though this matter has been well recognized as a cause of concern, limited data is available from ambulatory settings [1]. The prevalence of medicine use in children, both prescribed and over-the-counter (OTC) is reported to be high [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many subsequent studies proved this theory wrong. 2,3 Medicine use is among the most common health related activities children encounter during their day to day activities.…”
Section: Introductionmentioning
confidence: 99%